2022
DOI: 10.1111/rda.14088
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of freezing medium with encapsulated or free glutathione during cryopreservation of bull sperm

Abstract: Temperature and oxidative stress can increase radical oxygen species (ROS) in sperm, altering lipid and protein composition and decreasing sperm viability and motility during freezing and thawing (Cocuzza et al., 2007). To reduce free radical production and sperm damage during cryopreservation, various antioxidants, including free GSH, have been added to the semen extender. Reduced glutathione (GSH) is a very effective intracellular antioxidant due to its ability to scavenge free radicals (Donnelly et al., 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
(71 reference statements)
1
1
0
Order By: Relevance
“…Lorenzo-Torres et al [48] reported 122 nuclei in good-quality blastocysts produced by IVF. These results are lower than those obtained in the present study, but they are similar to those reported by Agata et al [49], Mastrorocco et al [50], and Nadri et al [51]. In the present study, before vitrification, treatments with 0.25 and 0.5 µM of resveratrol were statistically similar between them, although 0.5 µM showed the lowest number of nuclei, with 1 µM being the treatment that gave the highest number of nuclei in early blastocysts.…”
Section: Effect Of Resveratrol On Embryo Qualitysupporting
confidence: 85%
“…Lorenzo-Torres et al [48] reported 122 nuclei in good-quality blastocysts produced by IVF. These results are lower than those obtained in the present study, but they are similar to those reported by Agata et al [49], Mastrorocco et al [50], and Nadri et al [51]. In the present study, before vitrification, treatments with 0.25 and 0.5 µM of resveratrol were statistically similar between them, although 0.5 µM showed the lowest number of nuclei, with 1 µM being the treatment that gave the highest number of nuclei in early blastocysts.…”
Section: Effect Of Resveratrol On Embryo Qualitysupporting
confidence: 85%
“…Before semen cryopreservation, six semen samples were individually split into 4 equals and diluted to a final concentration of 6.0 × 10 7 /ml spermatozoa with the basic extender supplemented with 0 μg/ml SeNPs and 0 mM GSH (negative control group, NC), 2 μg/ml SeNPs (SeNPs group) ( 27 ), 4 mM GSH (GSH group) ( 50 ) and 4 mM GSH plus 2 μg/ml SeNPs (GSH + SeNPs group). Dose selections for GSH were conducted according to previous publications ( 5 , 56 ).…”
Section: Methodsmentioning
confidence: 99%